2009
DOI: 10.1002/qj.492
|View full text |Cite
|
Sign up to set email alerts
|

Potentially predictable patterns of extratropical tropospheric circulation in an ensemble of climate simulations with the COLA AGCM

Abstract: ABSTRACT:A variance decomposition approach to estimate the potentially predictable component of seasonal means has been further developed to separately diagnose the boundary-forced component and the slowly varying internal dynamics component. This decomposition of the potentially predictable component has been applied to an ensemble of ten 50-year simulations of the 500 hPa geopotential height field from the Center for Ocean-Land-Atmosphere Studies global atmospheric model forced by sea-surface temperatures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Such methods are based on the premise that the seasonal mean can be considered as a random variable, with a seasonal ''population'' mean and departures from that mean (Zheng and Frederiksen 2004;Frederiksen and Zheng 2007b). Zheng and Frederiksen (2004) referred to these two components as the slow and intraseasonal components of the seasonal mean.…”
Section: Introductionmentioning
confidence: 99%
“…Such methods are based on the premise that the seasonal mean can be considered as a random variable, with a seasonal ''population'' mean and departures from that mean (Zheng and Frederiksen 2004;Frederiksen and Zheng 2007b). Zheng and Frederiksen (2004) referred to these two components as the slow and intraseasonal components of the seasonal mean.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary intraseasonal modes of variability have mid-latitude wave-4 (DJF) or wave-3 (JJA) structures reflecting the impact on the seasonal mean of atmospheric blocking, the Madden-Julian oscillation, or the internal instability of the mid-latitude atmospheric flow. Subsequent studies (Zheng et al 2009;Grainger et al 2011b), found very similar modes of variability using ensembles of Atmosphere-only general circulation models (AGCMs). Grainger et al (2013) analysed the modes of variability in CGCMs from the coupled model intercomparison project phase 3 (CMIP3, Meehl et al 2007) dataset.…”
Section: Introductionmentioning
confidence: 85%
“…With an ensemble of general circulation model runs, it is possible to separate the internal variability in climate fields from influences associated with external forcing (Zheng et al 2009). For the CMIP5 CGCMs, the external forcing is associated with changes in anthropogenic greenhouse gases, aerosols, stratospheric ozone and land use; see Collins et al (2013) and references therein for forcing details.…”
Section: Modes Of Variabilitymentioning
confidence: 99%
See 2 more Smart Citations